Editorial: is enteral nutrition back in acute severe ulcerative colitis? Authors' reply. Issue 6 (18th February 2021) - Sahu, Pabitra; Kedia, Saurabh; Kumar Vuyyuru, Sudheer; Travis, Simon; Ahuja, Vineet
Abstract : LINKED CONTENT This article is linked to Sahu et al and Laharie papers. To view these articles, visit https://doi.org/10.1111/apt.16249 and https://doi.org/10.1111/apt.16260